Análise de métodos de avaliação social do ciclo de vida em organização pertencente a sistema de gerenciamento de resíduos sólidos urbanos - Mattos, Flavio Vassallo (2023)
Due to the problems caused on Earth by human activity, the search for sustainable development has arisen, thus the need to verify the Environmental, Economic and Social impacts of processes, products or services. In this context, the Life Cycle Assessment (LCA) methodology has emerged, specifically, Social Life Cycle Assessment (SLCA) to assess social impacts. In the development of LCA, different assessment methods were created and applied in various areas, including Municipal Solid Waste Management (MSWM) which, in developing countries, may include waste pickers. These people’s activities include the collection, sorting and sale of reusable and recyclable materials and they may be associated in Waste Pickers Organizations (WPO). Their purpose is environmentally correct, as they return to the production chain materials that would otherwise be sent to landfills or discarded in the environment. Accordingly, the goal of this study is to compare the results of five different SLCA methods applied to WPOs in Vitória, Espirito Santo State - Brazil. The performance of the methods to the results of the impacts were assessed in both subcategories and categories. The AHP Method and Likert Scale were also used to define a ranking of the stakeholder categories and subcategories by the importance, which supported the comparisons made. All the methods followed the Type I approach, using quantitative, qualitative and semi-quantitative data, obtained through field research, via interviews, online questionnaires and publicly available electronic data. The Worker category ranked the highest with MSWM experts, and also had the most subcategories and indicators (metrics) in the methods analyzed. The method used by Ibáñez-Forés and other authors was the most successful in evaluating the subcategories of the Worker category, while the Ciroth and Franze method fared better for the other subcategories. As for the category level, Ciroth and Franze's method was also the most successful at assessing WPOs. Therefore, due to the greater availability of secondary data, methods that use it can evaluate more subcategories and are more successful in comparing evaluations. Regarding the social impacts, the results of the different SLCA methods applied to WPO were not unanimous when using Performance Reference Points combined with a Type I approach.